Someone we know [large type] - Lapeña, Shari, 1960- (Random House Large Print, 2019)
"The new domestic suspense novel from NYT bestselling author Shari Lapena. Maybe you don't know your neighbours as well as you thought you did.... 'This is a very difficult letter to write. I hope you will not hate us too much... My son broke into your home recently while you were out.' In a quiet, leafy suburb in upstate New York, a teenager has been sneaking into houses--and into the owners' computers as well--learning their secrets, and maybe sharing some of them, too. Who is he, and what might he have uncovered? After two anonymous letters are received, whispers start to circulate, and suspicion mounts. And when a woman down the street is found murdered, the tension reaches its breaking point. Who killed her? Who knows more than they're telling? And how far will all these very nice people go to protect their little secrets? In this neighborhood, it's not just the husbands and wives who play games. Here, everyone in the family has something to hide..."--